Consumer Trust and Purchase Intention in E-Commerce Platforms: The Mediating Role of Perceived Value - Andi Cici Thania; Marito Ritonga; Sugianto Sugianto; Sunusi Dauda; Nabila Tijani Tharifah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid growth of e-commerce platforms has intensified competition and increased the importance of understanding factors that drive consumer purchase intention. This study examines the relationship between consumer trust and purchase intention in e-commerce platforms, emphasizing the mediating role of perceived value. Using a quantitative approach, data were collected from active e-commerce users and analyzed through structural equation modeling to evaluate both direct and indirect relationships among the constructs. The findings reveal that consumer trust significantly influences purchase intention by reducing perceived risk and enhancing confidence in online transactions. More importantly, perceived value serves as a key mediating mechanism that translates trust into favorable evaluative judgments regarding benefits, costs, and overall transaction worth. The results indicate that trust alone is insufficient to fully explain purchase intention without considering consumers’ value perceptions. This study contributes to e-commerce literature by offering an integrated trust–value–purchase intention framework and provides practical insights for platform managers to strengthen trust mechanisms while enhancing value propositions to foster sustainable consumer engagement and purchasing behavior.